China’s Energy Interests In Central Asia (The Journal of Interdisciplinary Human Studies, 2026)
This article analyses China’s strategic energy interests and policy in the Central Asian region. As China’s domestic demand for energy resources grows and the “Malacca Dilemma” persists along traditional maritime routes, Central Asia occupies an increasingly important place in Beijing’s energy diversification strategy. Drawing on energy security theory and Mackinder’s Heartland concept as analytical frameworks, the article examines China–Central Asia energy cooperation – with particular attention to the transition from conventional energy to renewable sources within the “Green Belt and Road Initiative.” A SWOT analysis is also applied to evaluate the strengths and weaknesses of this economic partnership, the opportunities it creates for regional states, and the geopolitical risks it entails, including the “debt trap” dynamic.
Keywords: Malacca Dilemma; Belt and Road Initiative; Green Belt and Road Initiative; Heartland theory; energy security theory; renewable energy; geopolitics; debt trap diplomacy; Central Asia